Peran Pengetahuan Perpajakan dan Religiusitas Terhadap Kepatuhan Wajib Pajak pada Usaha Mikro dan Kecil - Kais, Muhammad; Urumsah, Dekar; Rosita, Rosita (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2024)
Tax revenue is the primary source of national income, making tax compliance an important aspect in enhancing the potential of state tax revenues. By adopting attribution theory, this study aims to examine the influence of tax understanding, applicable tax sanctions, and religious beliefs (religiosity) on tax compliance among micro and small enterprises (MSEs) engaged in e-commerce, as well as gender and business age as moderating factors. A quantitative approach and SEM-PLS analysis were used to test the research model. The moderating effects of gender and business age were tested using multigroup analysis. The sample for this study consisted of 100 MSE taxpayers conducting electronic transactions in the Special Region of Yogyakarta. The results of this study show that tax understanding and religiosity have a positive effect on tax compliance in e-commerce SMEs. However, no empirical evidence was found to support the influence of tax sanctions on tax compliance. Furthermore, both gender and business age do not play a moderating role.